2023
DOI: 10.3390/agriculture13051027
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Use of an Immunomodulatory Feed Additive in Supplements for Grazing Young Nellore Bulls Transported after Weaning: Performance, Physiological, and Stress Parameters

Abstract: The objective of this study was to evaluate four different feeding strategies using an immunomodulatory feed additive for newly weaned Nellore cattle, before and after road transport, on their physiological parameters and performances during the growing phase of pastures. In total, eighty-four young Nellore bulls (initial BW = 174 ± 11 kg; 7 ± 1 months of age) were blocked by their initial body weights 42 days before road transport (d −42) and randomly assigned to one of the four supplementation strategies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…demonstrated no detrimental effects on production performances. Similarly, Batista et al [4], after supplementing immunomodulatory feed additives in weaned Nellore calves, found that their treatment had no effect on animal performance. Likewise, in Lefter et al study [5] on weaning piglets, probiotics supplements showed potential in enhancing production performance.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…demonstrated no detrimental effects on production performances. Similarly, Batista et al [4], after supplementing immunomodulatory feed additives in weaned Nellore calves, found that their treatment had no effect on animal performance. Likewise, in Lefter et al study [5] on weaning piglets, probiotics supplements showed potential in enhancing production performance.…”
mentioning
confidence: 95%
“…This study marks a significant step in unraveling clostridia prevention strategies, holding potential applications in enhancing biosecurity through animal diets. Batista et al [4] aimed to assess diverse strategies for supplementing immunomodulatory feed additives at (10 g/100 kg BW/day of NUTRA) before and after transportation in weaned Nellore calves raised on pasture and the subsequent impact on physiological parameters and performance as they progressed through the growth phase. Their findings suggest that the specific conditions of the experiment, such as the short duration of transportation stress and the relatively stress-free grazing environment, could have mitigated the detrimental effects of stress on the animals.…”
mentioning
confidence: 99%